Development of Ethnoscience-Based Physics Teaching Materials to Improve Students’ Argumentation Skills - Kariani, Kariani; Sukroyanti, Baiq Azmi; Habiburrahman, Lalu (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2025)
This study aims to develop ethnoscience-based physics teaching materials by integrating local cultural wisdom to enhance high school students’ argumentation skills. The development model employed is the 4D model: Define, Design, Develop, and Disseminate. The teaching materials were designed based on students' needs and characteristics. Validation results from two experts in content and media indicate that the materials are feasible for use, with feasibility scores of 75% and 83.3%, respectively. Revisions were suggested in terms of ethnoscience examples and layout design. The practicality test showed highly positive responses from teachers (85%) and positive responses from students (84.8%), indicating that the materials are easy to use and support meaningful learning. In terms of effectiveness, the average gain score was 21.797, with a symmetrical data distribution (skewness = -0.418) and normality (p = 0.163 based on the Shapiro-Wilk test). The Paired Samples t-Test showed a significant result (t = -11.669; p < 0.001), indicating a significant difference between the pre-test and post-test scores. The average N-Gain score of 0.777 is categorized as high, suggesting that the developed teaching materials effectively support students in constructing logical, structured, and evidence-based arguments.